Systematic Literature Review: Effectiveness of Laparoscopic Cholecystectomy on Service Efficiency and Length of Hospitalization - Duratul Fahlia; Dewi Purnamawati (SEAN Institute, 2026)
Gallstone disease is one of the most common gastrointestinal conditions requiring surgical intervention worldwide. Over the past few decades, laparoscopic cholecystectomy (LC) has replaced open cholecystectomy (OC) as the gold standard in gallbladder surgical management. Although its clinical advantages have been widely recognized, a systematic evaluation of its impact on hospital operational efficiency and resource optimization through length of stay is still needed. This study aims to evaluate the effectiveness of laparoscopic cholecystectomy in improving healthcare efficiency and shortening patient length of stay compared with open surgical procedures. This study used a Systematic Literature Review (SLR) method through a literature search in various scientific databases, such as PubMed, Scopus, and Google Scholar. The literature analyzed included meta-analyses, randomized clinical trials, and cohort studies comparing the outcomes of laparoscopic cholecystectomy and open cholecystectomy. A total of eight key journals were selected for further analysis, focusing on mortality, postoperative complications, length of stay, and healthcare cost-efficiency. The study showed that laparoscopic cholecystectomy significantly reduced mortality by 84% (RR 0.16) and reduced the risk of postoperative complications by 54% compared to open surgical procedures. In terms of service efficiency, this procedure was also shown to shorten the average length of stay by 4.08 days compared to open cholecystectomy. In several healthcare centers, the average length of stay for patients undergoing laparoscopic cholecystectomy was only around 2.1 days, compared to 5.6 days for open procedures. Furthermore, the implementation of ambulatory laparoscopic cholecystectomy has been proven safe, provides significant hospital cost savings, and improves patient satisfaction through a faster recovery process. Based on the study results, it can be concluded that laparoscopic cholecystectomy is more effective than open cholecystectomy in improving healthcare efficiency. The significant reduction in length of stay and the potential for outpatient procedures make this method an important strategy in optimizing hospital bed utilization and reducing healthcare system costs. Therefore, investment in infrastructure and development of laparoscopic services is highly recommended to increase accessibility of more efficient, safe, and high-quality surgical services.